It's all about the pentiums: The use, manipulation, and storage of digital microscopy imaging data for the biological sciences. Issue 7 (20th January 2014) - Hornick, Jessica E.; Hinchcliffe, Edward H.
SUMMARY: Digital microscopy has revolutionized quantitative imaging, with binary‐encoded computer files serving to capture and store imaging data sets for analysis. With the ever‐present use of computers to generate and store imaging data, it becomes increasingly important to understand how these files are created, and how they can be both used and mis‐used. This is a particularly important task for the biologist who may have limited background in computer science. Here we discuss some of the basic aspects of digital data storage and use, including file types, storage media, and the choice between commercial and open‐source software. Often, open‐source software is written by a user or group of users, and then distributed to the scientific community at large. These can be important tools, but there are some hidden costs to this freeware that we will discuss. We will also compare open‐source software to commercial imaging software, which is often written for use by non‐computer scientists. Mol. Reprod. Dev. 82: 508–517, 2015. © 2014 Wiley Periodicals, Inc .